Considerations for Sex-Cognizant Research in Exercise Biology and Medicine - O'Bryan, Samia M.; Connor, Kathleen R.; Drummer, Devin J.; Lavin, Kaleen M.; Bamman, Marcas M. (Frontiers in Sports and Active Living, 2022)
As the fields of kinesiology, exercise science, and human movement developed, the majority of the research focused on male physiology and extrapolated findings to females. This practice, also used in the medical sphere, resulted in the removal of drugs from the market in the late 1990s due to severe side effects (some life-threatening) in females that were not observed in males. In exercise medicine, exercise is being used as a drug to prevent, control, and treat disease. However, a literature knowledge base of predominantly male studies may leave the field vulnerable to overlooking key biological differences in males and females and, thus, inappropriately prescribing exercise. Critical considerations remain incompletely addressed (e.g., how exercise responses differ between sexes and whether there are optimal approaches to consider for females that differ from conventional approaches that are based on male physiology. Thus, this review will discuss anatomical, physiological, and skeletal muscle molecular differences that may contribute to sex differences in exercise responses, as well as clinical considerations based on this knowledge in athletic and general populations over the continuum of age. Finally, this review summarizes the current gaps in knowledge, highlights the areas ripe for future research, and considerations for sex-cognizant research in exercise fields.